2017
DOI: 10.1002/met.1655
|View full text |Cite
|
Sign up to set email alerts
|

Bias correction of climate models for hydrological modelling – are simple methods still useful?

Abstract: The spatial climatic characteristics of the Himalayas are complex and a challenge for regional climate models (RCMs). There is no doubt that some form of correction before any application of RCM simulations is a must. In recent years, simple bias correction techniques have been overshadowed by more popular and complex bias correction techniques. In this study an attempt is made to compare the performance of a simple and of a comparatively complex correction technique for hydrological analysis at a monthly reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(77 citation statements)
references
References 25 publications
3
73
0
1
Order By: Relevance
“…In general, linear scaling (LS) yielded better results for mean monthly flow simulations, followed by parametric (except QMS) and nonparametric quantile mapping techniques. Similar results have been reported over Kaligandaki River basin, Nepal (Shrestha et al ., ). The assessment of these individual bias correction techniques over the independent testing period also confirms an advantage of monthly over annual approach, as presented in Table S1, Supporting Information.…”
Section: Resultsmentioning
confidence: 97%
“…In general, linear scaling (LS) yielded better results for mean monthly flow simulations, followed by parametric (except QMS) and nonparametric quantile mapping techniques. Similar results have been reported over Kaligandaki River basin, Nepal (Shrestha et al ., ). The assessment of these individual bias correction techniques over the independent testing period also confirms an advantage of monthly over annual approach, as presented in Table S1, Supporting Information.…”
Section: Resultsmentioning
confidence: 97%
“…Similar results were obtained by Teutschbein and Seibert [69] in their evaluation of several bias correction methods over five Swedish catchments using 15 different RCMs driven by ERA40, where LS resulted in slightly larger model error growth and deviations compared to more advanced correction methods such as QM, which makes LS the least reliable method under changed conditions. In contrast, Shrestha et al [110] found no significant differences between the performances of LS and EQM bias corrected outputs for the Kaligandaki River Basin in Nepal. Such discrepancies however, are most likely related to substantial climatic differences between the Himalayas, Sweden and the Central-American tropics.…”
Section: Sonmentioning
confidence: 87%
“…The full amount of these complex factors could also explain why DT, being simpler than the remaining BC methods, normally exhibits better performances than more complex methods such as EQM or GPQM for the North and Caribbean regions, which could also be limited to monthly temporal resolution data as suggested by Yang et al [47], Shrestha et al [110] and Hanel et al [111]. Nevertheless, the diminished GCM-RCM model performances in terms of R and PBIAS does not necessarily indicate severe model biases but rather shows that GCM-RCM pairs cannot properly reproduce JJA monthly deviations within the annual precipitation distribution cycle.…”
Section: Jjamentioning
confidence: 99%
“…For example, previous studies examining the performance of the Weather Research and Forecasting (WRF) model at high resolution in the HKKH region have typically focused on either one small river catchment or over larger regions that considered only a limited number of in situ measurements for relatively short periods of time of 1 year or less (Bonekamp et al, ; Collier & Immerzeel, ; Li et al, ; Maussion et al, ; Norris et al, ; Orr et al, ), therefore failing to fully assess the model's ability to reproduce the actual detailed patterns of precipitation. Furthermore, though multiple studies have shown the importance of bias correction of precipitation over topographically complex regions (e.g., Bordoy & Burlando, ; Lafon et al, ; Teutschbein & Seibert, ), the usefulness of such methods over the HKKH has yet to be conclusively proven (Shrestha et al, ).…”
Section: Introductionmentioning
confidence: 99%